Remittances, investment and new emigration trends in Kerala - Sunny, J., Parida, J.K. and Azurudeen, M. (Review of Development and Change)
This article reports a study of the interlinkages among remittance receipts, household-level investment and the changing emigration patterns in Kerala, using seven rounds of the Kerala Migration Survey conducted between 1998 and 2018. The major findings suggest that remittances improved households$1 (Bper capita income and changed their spending patterns. Households receiving remittance, on average, spare a relatively larger share of monthly income on the consumption of non-food durable goods. Moreover, receipts of remittance also enable the households to save, to invest more on assets, land and buildings, and to form human capital (through increased share of spending on education and health). Households which devote a large share of spending on education and health also report a relatively high share of skilled emigration to either Global North or Oceania regions, instead of the traditional low-skilled Gulf emigration. Hence, policies that help boost these new emigration trends are likely to sustain the growth of remittance inflows and the process of overall socio-economic development in Kerala.- Reproduced s
Keywords: Remittances, Household spending, Human capital formation, Skilled emigration